THE ROLE OF PARENTS IN ESTABLISHING INDEPENDENCE EARLY CHILDHOOD - Ratna Purwanti; Muhammad Saleh; Zulfa Fardhinah (PEDAGOGIA, 2022)
Parents become one of the important roles in the family environment in the strengthening of character. The thing that needs to be given special attention in strengthening this character is parental guidance in order to facilitate the potential of the child. Parents must work together to have knowledge and experience about instilling good values in children such as independence. This research was conducted using quantitative methods. Group B parents were the population and samples in this study. The data collection technique used is a questionnaire with a data analysis technique using percentage calculations. The results of the study provide a positive understanding of children categorized as very good, educate children accustomed to be neatly categorized as good, provide games that can form children's independence categorized as very good, get children used to behaving in accordance with good manners and motivate children not to be lazy to be categorized as good. These five aspects of the study greatly affect the independence of children at home.